Fear of missing out(FOMO) and the usage of social media towards young adults in Malaysia - Koo, Kai Yan (2023)
This study is conducted to understand the relationship between social media usage and Fear of Missing Out (FOMO) among the young Malaysian adults. Humans are natural social beings and with the advance of technology, smartphones become an indispensable invention to allow connection with everyone in our daily life. The given privilege to constantly connect with people, especially through social media results to excessive use which could interfere with one’s well-being, especially with the apprehension of FOMO. With the insufficient data understanding FOMO’s manifestation, behaviours and well-being of Malaysian users on Instagram, this study aims to provide further clarification in users behaviours in Instagram in relation to FOMO through data collection using questionnaire. This will provide further data to understand the influences that can impact the wellbeing of young adults. The study purpose is to find out the types of FOMO available in Malaysia young adults and to analyse the relationship between FOMO and social media usage on young adults in Malaysia. A total of 51 participants are being survey based on a questionnaire and data collected in analyze through google form and r software. Results show there is up to 60% participants having FOMO and there is positive correlation between social media usage with FOMO. Future study with implementation in gender differences and ethnicity variant can be explore for wider perspective.